KARAKTERISTIK INFORMAL VALUE TRANSFER SYSTEM SEBAGAI FAKTOR KRIMINOGEN TERJADINYA PRAKTEK MONEY LAUNDERING DAN KEGIATAN PEMBIAYAAN TERORISME - Damanik, Yosef Darman (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2013)
AbstractInformal value transfer system is a money transfer system that is already operating before the presence of the formal financial system. Remittance system was originally used to facilitate illegal activities, but this time, the system is actually used by criminals to commit money laundering and financing of terrorism. Characteristics possessed by money transfer system has made this system as a factor contributing to the crime of money laundering and financing of terrorism committed by criminals.Keywords: informal value transfer system, money laundering, financing of terorism.